2002
DOI: 10.1017/s0031182002002196
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential protective antigens of Ostertagia ostertagi with local antibody probes

Abstract: The identification of protective helminth antigens remains the most important challenge in the development of parasitic vaccines. To identify protective antigens of Ostertagia ostertagi, an important abomasal parasite of cattle, parasite-specific local antibodies from the abomasal mucus and from the draining lymph nodes were collected from calves immunized with multiple infections and from 'primary infected' animals. With these probes, Western blots of extracts and excretion/ secretion (E/S) material from L3, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 0 publications
0
12
0
1
Order By: Relevance
“…Another group of proteins, that represented 10% of the proteins identified in the EV-enriched material and have not been previously identified in exosomes of other organisms, are ‘nematode ES proteins’ ascribed no specific function on the basis of the absence of characteristic motifs in their sequences. However, TDP01869 was found to share homology with the H. contortus 15 kDa ES protein ( Schallig et al, 1997b ); HCP02856, HCP06214 and TDP00176 homologues of the T. circumcincta 20 kDa ES protein ( Nisbet et al, 2013 ); OOP00884, TDP00436 and TDP00589 homologues of the O. ostertagi ‘putative L3 ES protein’ ( De Maere et al, 2002 ); and TDP00713 homologue of the T. colubriformis 30 kDa glycoprotein ( Savin et al, 1990 ). Each of the homologous proteins ( H. contortus 15 kDa ES protein, T. circumcincta 20 kDa ES protein, O. ostertagi ‘putative L3 ES protein’ and T. colubriformis 30 kDa glycoprotein) has been described as a vaccine candidate in previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another group of proteins, that represented 10% of the proteins identified in the EV-enriched material and have not been previously identified in exosomes of other organisms, are ‘nematode ES proteins’ ascribed no specific function on the basis of the absence of characteristic motifs in their sequences. However, TDP01869 was found to share homology with the H. contortus 15 kDa ES protein ( Schallig et al, 1997b ); HCP02856, HCP06214 and TDP00176 homologues of the T. circumcincta 20 kDa ES protein ( Nisbet et al, 2013 ); OOP00884, TDP00436 and TDP00589 homologues of the O. ostertagi ‘putative L3 ES protein’ ( De Maere et al, 2002 ); and TDP00713 homologue of the T. colubriformis 30 kDa glycoprotein ( Savin et al, 1990 ). Each of the homologous proteins ( H. contortus 15 kDa ES protein, T. circumcincta 20 kDa ES protein, O. ostertagi ‘putative L3 ES protein’ and T. colubriformis 30 kDa glycoprotein) has been described as a vaccine candidate in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the T. circumcincta 20 kDa ES protein (Tci-ES20) is one of the components of the eight-protein recombinant ‘cocktail’ mentioned above ( Nisbet et al, 2013 ). The O. ostertagi ‘putative L3 ES protein’ has been proposed as potential protective antigen because it was bound by antibodies from “immune” calves ( De Maere et al, 2002 ), but it remains to be tested in an immunisation trial. Putative functions for the above proteins remain to be established; however, their involvement in several successful vaccine trials indicates their potential as valid candidates.…”
Section: Discussionmentioning
confidence: 99%
“…SXC domains have also been identified in other helminths such as Ascaris, Brugia , Trichuris muris and Necator [88]. The function of the motif is not known but it is suggested that it is involved in protein-protein interactions, particularly those associated with nematode surfaces [89] or that it acts as a signalling ligand [90]. In general, SXC motif containing proteins have a putative secretory signal peptide and are therefore extracellular.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccine protection relies on the presence of high levels of anti-ASP IgE (Kooyman et al, 2000). (2) Antibodies obtained from the abomasal mucus and draining lymph nodes from calves immunized with multiple infections of Ostertagia ostertagi recognize an ASP orthologue (De Maere et al, 2002). In addition fractions of helminth antigens that protect cattle against O. ostertagi infection are enriched in single domain ASPs (Geldhof et al, 2003).…”
Section: Ancylostoma Secreted Proteinsmentioning
confidence: 99%
“…MTP-1 is an immunodominant protein and was first cloned and isolated by screening an A. caninum cDNA expression library with pooled sera from hookworm-infected individuals who harbor low worm burdens and are putatively resistant (Zhan et al, 2002a). Calves immunized with O. ostertagi L3 also recognize an MTP-1 orthologue (De Maere et al, 2002). Studies examining the vaccine potential of Ac-MTP-1 from A. caninum are under evaluation, as is an orthologue from Ancylostoma ceylanicum (see below).…”
Section: Astacin-like Metalloprotease (Mtp)mentioning
confidence: 99%